Empowering Young Learners: A Study of Intrinsic and Extrinsic Motivation to Learn English in Junior High School - Titin Nurhayati; Paulus Kuswandono; Ouda Teda Ena (Jurnal Studi Guru dan Pembelajaran, 2024)
The main issue in this research is how to determine the dominant type of motivation perceived by junior high school students in learning English, and how the factors of self-satisfaction and obligation shape students' intrinsic and extrinsic motivation in the process of learning English. The research aims to know the dominant motivation type perceived by junior high schools in learning English and how self-satisfaction and obligation shape the students’ intrinsic and extrinsic motivation to learn English. This research employed a mixed method that combines the quantitative and qualitative data. The researchers used a closed-ended questionnaire and semi-structured interview to gather the data. The data from the questionnaire were analyzed by calculating the mean of each statement. The Likert scale was applied to assess the level and type of student's motivation to learn English. At the same time, the interview data were analyzed. The participants of this research were 60 students of SMP N 1 Selopampang Temanggung. The findings showed the students’ extrinsic motivation to learn English is at a high level, while the students’ intrinsic motivation is at a moderate level. Moreover, intrinsic motivation is influenced by self-satisfaction and excitement. However, extrinsic motivation is a combination of control regulation style and self-satisfaction. Hence obligation is the factor that can drive the individual to self-satisfaction. The finding of this research would impact the teacher in teaching media, material, and strategies selected to increase the student's learning motivation and reduce the students' learning loss.